1996
DOI: 10.1542/peds.97.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Amyoplasia, the Most Common Type of Arthrogryposis: The Potential for Good Outcome

Abstract: Background. Amyoplasia is the most commonly seen diagnostic subgroup of children with arthrogryposis. The natural history of these children has not been well described previously. Methods. Review of the medical records of 38 children with amyoplasia enabled us to describe their birth characteristics, therapeutic interventions, and functional outcomes. Results. Eighty-four percent of the children had symmetrical, four-limb involvement, which was similar to the original descriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The diagnostic criteria for amyoplasia are highly specific, with decreased muscle mass, typical joint contractures, and limb positioning at birth, mostly symmetrical in all four limbs. There may be involvement only of the lower limbs or, less commonly, only of the upper limbs and asymmetric limb involvement [1, 33]. Typically, the shoulders are adducted and internally rotated, and the elbows are extended with the forearms pronated and wrists and fingers flexed.…”
Section: Amyoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic criteria for amyoplasia are highly specific, with decreased muscle mass, typical joint contractures, and limb positioning at birth, mostly symmetrical in all four limbs. There may be involvement only of the lower limbs or, less commonly, only of the upper limbs and asymmetric limb involvement [1, 33]. Typically, the shoulders are adducted and internally rotated, and the elbows are extended with the forearms pronated and wrists and fingers flexed.…”
Section: Amyoplasiamentioning
confidence: 99%
“…The feet are most often in an equinovarus adductus position, although other types of foot deformities occur. Involvement of the spine is also described [1, 33]. The contractures can be fixed or flexible.…”
Section: Amyoplasiamentioning
confidence: 99%
“…The involvement of upper extremities with inability of hand and arm support has also been found to influence walking function [10, 11]. Most children with AMC can achieve functional ambulation and 85% have been reported as ambulators by the age of 5 years, but for efficient community ambulation, a wheelchair may be required [3, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Another small-scale study of 38 pediatric patients with amyoplasia found the rate of surgery to be 24% elbow, 16% wrist, 8% hand, 5% spine, 18% hip, 39% knee, and 76% feet with an average of 5.7 surgeries per child. 22 Our study of a larger population found a higher rate of upper extremity, spine, and hip surgery and a lower rate of knee and foot surgery in patients with amyoplasia. Additionally, our study found a lower average number of surgeries (1.9 total surgeries).…”
Section: Discussionmentioning
confidence: 50%